Dendritic Cells in the Periphery Control Antigen-Specific Natural and Induced Regulatory T Cells - Yamazaki, Sayuri; Morita, Akimichi (Frontiers in Immunology, 2013)
Dendritic cells (DCs) are specialized antigen-presenting cells that regulate both immunity and tolerance. DCs in the periphery play a key role in expanding naturally occurring Foxp3+ CD25+ CD4+ regulatory T cells (Natural T-regs) and inducing Foxp3 expression (Induced T-regs) in Foxp3- CD4+T cells. DCs are phenotypically and functionally heterogeneous, and further classified into several subsets depending on distinct marker expression and their location. Recent findings indicate the presence of specialized DC subsets that act to expand Natural T-regs or induce Foxp3+T-regs from Foxp3- CD4+T cells. For example, two major subsets of DCs in lymphoid organs act differentially in inducing Foxp3+T-regs from Foxp3- cells or expanding Natural T-regs with model-antigen delivery by anti-DC subset monoclonal antibodies in vivo. Furthermore, DCs expressing CD103 in the intestine induce Foxp3+T-regs from Foxp3- CD4+T cells with endogenous TGF-β and retinoic acid. In addition, antigen-presenting DCs have a capacity to generate Foxp3+T-regs in the oral cavity where many antigens and commensals exist, similar to intestine and skin. In skin and skin-draining lymph nodes, at least six DC subsets have been identified, suggesting a complex DC-T-reg network. Here, we will review the specific activity of DCs in expanding Natural T-regs and inducing Foxp3+T-regs from Foxp3- precursors, and further discuss the critical function of DCs in maintaining tolerance at various locations including skin and oral cavity.